Assessing quality of life in psychosocial and mental health disorders in children: a comprehensive overview and appraisal of generic health related quality of life measures - Jochen O. Mierau; Daphne Kann-Weedage; Pieter J. Hoekstra; Lisan Spiegelaar; Danielle E. M. C. Jansen; Karin M. Vermeulen; Sijmen A. Reijneveld; Barbara J. van den Hoofdakker; Erik Buskens; M. Elske van den Akker-van Marle; Carmen D. Dirksen; Annabeth P. Groenman (BMC, 2020)
Abstract Background Mental health problems often arise in childhood and adolescence and can have detrimental effects on people's quality of life (QoL). Therefore, it is of great importance for clinicians, policymakers and researchers to adequately measure QoL in children. With this review, we aim to provide an overview of existing generic measures of QoL suitable for economic evaluations in children with mental health problems. Methods First, we undertook a meta-review of QoL instruments in which we identified all relevant instruments. Next, we performed a systematic review of the psychometric properties of the identified instruments. Lastly, the results were summarized in a decision tree. Results This review provides an overview of these 22 generic instruments available to measure QoL in children with psychosocial and or mental health problems and their psychometric properties. A systematic search into the psychometric quality of these instruments found 195 suitable papers, of which 30 assessed psychometric quality in child and adolescent mental health. Conclusions We found that none of the instruments was perfect for use in economic evaluation of child and adolescent mental health care as all instruments had disadvantages, ranging from lack of psychometric research, no proxy version, not being suitable for young children, no age-specific value set for children under 18, to insufficient focus on relevant domains (e.g. social and emotional domains).